Integrated transcriptome and proteome analysis reveals molecular responses of soybean anther under high-temperature stress - Li, Jiajia; Chen, Linying; Zhi, Xianguan; Wang, Jianxin; Lu, Yun; Tian, Zhuo; Wu, Meiyan; Shan, Yajing; Chen, Haoran; Liao, Wei; Long, Qun; Zhu, Shangshang; et al. (Frontiers in Plant Science, 2023)
It is well documented that high temperature (HT) severely impacts on the development of soybean male reproductive organs. However, the molecular mechanism of thermo-tolerance in soybean remains unclear. To explore the candidate genes and regulatory mechanism of soybean response to HT-stress and flower development, here, the anthers of previously identified two varieties of HT-tolerant (JD21) and HT-sensitive (HD14) were analyzed by RNA-seq. In total, 219 (172 up-regulated and 47 down-regulated), 660 (405 up-regulated and 255 down-regulated) and 4854 (2662 up-regulated and 2192 down-regulated) differentially expressed genes (DEGs) were identified between JD21 anthers treated with HT-stress vs JD21 anthers in the natural field conditions (TJA vs CJA), HD14 anthers treated with HT-stress vs HD14 anthers in the natural field conditions (THA vs CHA), and JD21 vs HD14 anthers treated with HT-stress (TJA vs THA), respectively. The resulted showed that there were more DEGs were up-regulated in JD21, this might be the reason why JD21 was more HT-resistant than HT-sensitive variety HD14. GO annotation and KEGG enriched analysis showed that many DEGs are mainly involved in defense response, response to biological stimuli, auxin activated signaling pathway, plant hormone signal transduction, MAPK signaling pathway-plant, starch and sucrose metabolism, etc. The conjoint analysis of RNA-seq and previous iTRAQ results found that there were 1, 24, and 54 common DEGs/DAPs showing the same expression pattern and 1, 2 and 13 DEGs/DAPs were opposite common between TJA vs CJA, THA vs CHA and TJA vs THA at the protein and gene level, respectively, among which main including HSPs, transcription factor, GSTU and other DEGs/DAPs participated in the response to HT stress and flower development. Notably, the qRT-PCR analysis and physiological index change results were coincided with the sequencing results of RNA-seq and iTRAQ. In conclusion, the HT-tolerant cultivar exhibited better under stress than HTt-sensitive cultivar through modulation of HSP family proteins, transcription factors, and keep key metabolic pathways such as plant hormone signal transduction normal. This study provided important data and some key candidate genes for better studying the effect and molecular basis of HT on anther in soybean at a transcription and translation level.